Economic and Mathematical Modeling of the Quality of Services Provided by the Urban Passenger Transport Infrastructure Us-ing Nonfinancial Indicators - Sekerin, Vladimir; Dudin, Mikhail; Shevchenko, Dmitri; Zadornov, Konstantin; Maleeva, Diana (International Journal of Engineering and Technology, 2018)
The article reviews the issues of justifying the expediency of using financial indicators to assess the quality of passenger transportation and identification of the main factors that influence the quality of transportation. An economic and mathematical model of the passenger transportation quality using nonfinancial indicators was developed in the study.It was proposed to use a mathematical toolkit of the theory of queuing systems (QS) to study the operation of the route of the urban passenger transport system (UPTS).Â Â